Active membrane transport and receptor proteins from bacteria. (1st August 2005) - Saidijam, M.; Bettaney, K.E.; Szakonyi, G.; Psakis, G.; Shibayama, K.; Suzuki, S.; Clough, J.L.; Blessie, V.; Abu-bakr, A.; Baumberg, S.; Meuller, J.; Hoyle, C.K.; et al.
Abstract : A general strategy for the expression of bacterial membrane transport and receptor genes in Escherichia coli is described. Expression is amplified so that the encoded proteins comprise 5–35% of E. coli inner membrane protein. Depending upon their topology, proteins are produced with RGSH6 or a Strep tag at the C-terminus. These enable purification in mg quantities for crystallization and NMR studies. Examples of one nutrient uptake and one multidrug extrusion protein from Helicobacter pylori are described. This strategy is successful for membrane proteins from H. pylori, E. coli, Enterococcus faecalis, Bacillus subtilis, Staphylococcus aureus, Microbacterium liquefaciens, Brucella abortus, Brucella melitensis, Campylobacter jejuni, Neisseria meningitides, Streptomyces coelicolor and Rhodobacter sphaeroides .